2007
DOI: 10.1186/1472-6963-7-68
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of a decentralized budget on physicians' compliance with guidelines for statin prescription – a multilevel methodological approach

Abstract: Background: Official guidelines that promote evidence-based and cost-effective prescribing are of main relevance for obvious reasons. However, to what extent these guidelines are followed and their conditioning factors at different levels of the health care system are still insufficiently known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 30 publications
1
38
1
Order By: Relevance
“…In 2003 adherence to guidelines increased with age of the patients, but in 2005 there 9 were no differences between age groups. Older locum physicians presented a lower probability of prescribing a recommended statin than older GPs Model A in table 3, only includes two levels (i.e., patients and HCCs) and shows that in median a randomly selected patient's odds of receiving a recommended statin would increase of Scania [9]. However, the current analysis also adds information regarding the physician level.…”
Section: Multi-level Regression Modelsmentioning
confidence: 65%
See 4 more Smart Citations
“…In 2003 adherence to guidelines increased with age of the patients, but in 2005 there 9 were no differences between age groups. Older locum physicians presented a lower probability of prescribing a recommended statin than older GPs Model A in table 3, only includes two levels (i.e., patients and HCCs) and shows that in median a randomly selected patient's odds of receiving a recommended statin would increase of Scania [9]. However, the current analysis also adds information regarding the physician level.…”
Section: Multi-level Regression Modelsmentioning
confidence: 65%
“…Despite these recommendations several studies have demonstrated substantial and unexplained differences in the adherence with guidelines among physicians and among Health Care Centres (HCC) [8,9,12,13].These differences might express themselves as a clustering of similar prescription behavior among physicians at the same HCC and suggest the existence of local therapeutic traditions. Quantifying and understanding this variation is relevant for the planning of interventions aimed to improve the 4 quality of drug prescription.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations